Functions and characteristics of corporate and sovereign CDS - Heinz-Dieter Vogel; Christina E. Bannier; Thomas Heidorn (Frankfurt School of Finance & Management, 2013)
After the onset of the subprime crisis and the European debt crisis, credit default swaps (CDS) have seen a strong increase in usage. Particularly sovereign CDS protection has been sought after, paralleling the rise in sovereign debt levels, slumps in GDP growth and political tensions in Eurozone peripheral countries. Understanding the strengths and weaknesses of CDS products has hence become ever more important, from both the perspective of individual market participants and regulatory bodies. This paper gives an overview of the origins and characteristics of CDS products by discussing the various stages of the product life-cycle. In a second step, we investigate the development and functioning of the CDS market. We focus particularly on the differences between corporate and sovereign CDS and provide insights into the respective structure of market participants, means of product usage and regulatory conditions.
Keywords: G12; 330; Credit default swaps; European sovereign CDS; Corporate CDS